Implementation of Rainwater Harvesting for Urban Flood Control in the Karang Asam Kecil Watershed - Muslimin, Muhammad Syahrizal; Suharyanto; Wulandari, Dyah Ari (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
95 masl and is often flooded. This study aims to evaluate the effectiveness of the implementation of Low Impact Development with rainwater harvesting as the main method in reducing surface runoff in the Karang Asam Kecil watershed. Rainwater harvesting modeling is applied to 9 subcatchments with an application of 100 m2/unit. Simulation using the Storm Water Management Model (SWMM) with a 10-year return period rainfall shows that surface runoff in existing conditions is 45.632 mm. Meanwhile, after the implementation of rainwater harvesting, it decreased to 18.814 mm, or decreased by 58.77%. These results indicate that rainwater harvesting is effective in reducing surface runoff and can be a solution to flood mitigation in the Karang Asam Kecil watershed.